A gene regulatory network controls the binary fate decision of rod and bipolar cells in the vertebrate retina - Wang, Sui (Dev Cell, 2014)
Gene regulatory networks (GRNs) regulate critical events during development. In complex tissues, such as the mammalian central nervous system (CNS), networks likely provide the complex regulatory interactions needed to direct the specification of the many CNS cell types. Here we dissect a GRN that regulates a binary fate decision between two siblings in the murine retina, the rod photoreceptor and bipolar interneuron. The GRN centers on Blimp1, one of the transcription factors (TFs) that regulates the rod versus bipolar cell fate decision. We identified a cis-regulatory module (CRM), B108, which mimics Blimp1 expression. Deletion of genomic B108 by CRISPR/Cas9 in vivo using electroporation abolished the function of Blimp1. Otx2 and RORβ were found to regulate Blimp1 expression via B108, and Blimp1 and Otx2 were shown to form a negative feedback loop that regulates the level of Otx2, which regulates the production of the correct ratio of rods and bipolar cells.